2020
DOI: 10.30773/pi.2019.0084
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Temperament and Character with Coping Strategies among Office Workers

Abstract: while younger adults may use support seeking or problem-focused coping strategies. 5 Among the various factors related to choosing a coping strategy, personality plays a major role. [6][7][8][9][10] Personality is, broadly speaking, described as a series of common behavioral, cognitive, and emotional patterns in an individual that stems from biological and environment aspects. 11 Although there are multiple viewpoints and ways to quantify personality, one widely used model is Cloninger's Psychobiological Model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
(83 reference statements)
1
1
0
Order By: Relevance
“…The mediation analysis showed that social support could be a partial mediator for postpartum depressive symptoms in high HA subjects, but not in low SD subjects. One possible explanation is the use of different coping strategies between high HA and low SD subjects, which is supported by a recent study using office workers (46). This study suggests low HA is associated with problem-focused coping skills, whereas low SD is associated with emotion-focused coping skills.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The mediation analysis showed that social support could be a partial mediator for postpartum depressive symptoms in high HA subjects, but not in low SD subjects. One possible explanation is the use of different coping strategies between high HA and low SD subjects, which is supported by a recent study using office workers (46). This study suggests low HA is associated with problem-focused coping skills, whereas low SD is associated with emotion-focused coping skills.…”
Section: Discussionsupporting
confidence: 71%
“…Future study which examines social support specifically affect these specific factors of EPDS is needed. In contrast, high SD subjects had difficulty in utilizing emotion-focused coping skills ( 46 ), and thus their depressive symptoms might be independent of the availability of social support. Intensive psychological care, such as cognitive behavioral therapy, might be effective for those subjects, rather than an increase in social support ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%